1986
DOI: 10.1210/endo-118-4-1476
|View full text |Cite
|
Sign up to set email alerts
|

Relaxin on Induction of Parturition in Beef Heifers*

Abstract: Purified porcine relaxin (3000 U/mg) was administered into the cervical os of primiparous beef heifers on day 278 of gestation (approximately 5 days before parturition normally occurs) to determine its effects on the induction of parturition, changes in progesterone, estrone (E1), 17 beta-estradiol (17 beta-E2), cervical dilation, and pelvic relaxation. Heifers were assigned randomly to 1 of 3 treatments: relaxin-double (two infusions of 3000 U, 12 h apart; n = 17), relaxin-single (3000 U; n = 14), and PBS-gel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
29
2

Year Published

1987
1987
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 38 publications
(50 reference statements)
9
29
2
Order By: Relevance
“…30 The choice of VSMCs of bovine origin was motivated by the fact that these cells retain a distinct muscular phenotype in in vitro culture, including the ability to produce NO, 30 and that porcine RLX has been found to be active in cattle heifers in vivo. 50 Smooth muscle tissue strips were explanted from bovine aortas and placed in tissue-culture flasks. The tissue strips were then incubated in DMEM plus 10% FCS until the SMCs, which had spread from the explants, reached confluence.…”
Section: Cell Culturementioning
confidence: 99%
“…30 The choice of VSMCs of bovine origin was motivated by the fact that these cells retain a distinct muscular phenotype in in vitro culture, including the ability to produce NO, 30 and that porcine RLX has been found to be active in cattle heifers in vivo. 50 Smooth muscle tissue strips were explanted from bovine aortas and placed in tissue-culture flasks. The tissue strips were then incubated in DMEM plus 10% FCS until the SMCs, which had spread from the explants, reached confluence.…”
Section: Cell Culturementioning
confidence: 99%
“…The combined induction resulted in reduced intervals between drug treatment and calving, shortened the calving period, reduced the incidence and severity of dystocia, reduced the proportion of heifers with retained placenta as well as the duration of retained placenta. These events were preceded by an accelerated decrease of plasma progesterone, and pelvic and cervical relaxation in much the same manner as reported earlier (Musah et al, 1986a,b).In this study, the profile of plasma peripheral progesterone levels during the periparturient period was similar to those observed during the periparturient period associated with normal calving, relaxin facilitated calving, prostaglandin or glucocorticoid induced calving (Johnson and Jackson, 1982;Musah et al, 1986a). Relaxin alone or combined with cloprostenol and dexamethasone is associated with luteal demise, consistent with earlier reports (Musah et al, 1986a).…”
supporting
confidence: 89%
“…This study indicates that a combined treatment of relaxin with cloprostenol or dexamethasone reduced the incidence and severity of dystocia due to increased cervica^. and pelvic relaxation (Musah et al, 1986b) as well as reduced the incidence of retained placenta as reported earlier (Musah et al, 1986a).The mechanisms by which relaxin may reduce retained placenta are unknown* The maternal and fetal connective tissue in placentome becomes progressively collagenized up to the time of parturition. At the onset of parturition, the tissue of the placentome becomes loose, a process that is essential for expulsion of the fetal membranes (Grunert, 1980).…”
mentioning
confidence: 53%
See 2 more Smart Citations